Effectiveness of Using Problem-Based Electronic Modules on Agreement Materials for Students - Ulfa Fauziah, Hamidah; Sekarsari , Peni; Sasmita , Wikan; Qaisya Huda , Fadilla (IJCER (International Journal of Chemistry Education Research), 2024)
This research aims to develop and test the effectiveness of a problem-based e-module assisted by a flipbook maker application for contract legal materials. A problem in civil and business law is something that must be studied by students in order to be able to resolve or solve a problem through the scientific method stage. This research uses the writing and development procedures proposed by Borg and Gall. The development study produced a product in the form of a problem-based e-module assisted by a flipbook maker with effective contract law materials. The product effectiveness test was based on the results of a large group test, namely the average pre-test score was 57.82 while the post-test score was 72.05. This shows an increase in the average obtained by students, namely 14.23.